The Legal World of Unmarried Couples: Reflections on "De Facto Relationships" in Recent New Zealand Legislation - Atkin, Bill (Victoria University of Wellington Law Review, 2008)
This article is a revised version of a paper presented at a conference in Vienna 16-20 September 2008, the 13th World Conference of the International Society of Family Law. The paper notes how the New Zealand legislation for most purposes equates the legal position of de facto, civil union and married couples. The main part of the paper focuses on the key definition of "de facto relationship" and draws attention in particular to the leading High Court decision of Scragg v Scott. While there will inevitably be borderline situations, most are likely to fall easily within or outside the definition. It is very fitting to have in this issue of the Law Review a piece by Professor Atkin on New Zealand’s relationship property law: in the 1970s when the original matrimonial property statute was enacted, Professor Angelo and Professor Atkin together made submissions to Parliament and subsequently co-authored articles on the subject.